2017
DOI: 10.1177/1535370217724791
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Serum [Met5]-enkephalin levels are reduced in multiple sclerosis and restored by low-dose naltrexone

Abstract: This report presents human and animal data identifying a novel biomarker for the onset and progression of multiple sclerosis (MS). Humans diagnosed with MS have reduced serum levels of OGF (i.e. [Met 5 ]-enkephalin) relative to non-MS neurologic patients, and low-dose naltrexone (LDN) therapy restored their enkephalin levels. Serum OGF levels were reduced in mice immunized with MOG 35-55 prior to any clinical behavioral sign of experimental autoimmune encephalomyelitis, and LDN therapy restored their serum O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…Treatment with OGF or LDN restored serum enkephalin levels to normal and often correlated with reduced clinical behavior and restored sensitivity to pain and heat in mice. The animal work facilitated measurement of serum enkephalins in a longitudinal manner and was able to demonstrate that normal animals inoculated with MOG antigen expressed decreased enkephalins as the disease progressed (47,48). This work is the first to suggest that OGF (chemically termed [Met 5 ]-enkephalin) may be a specific marker for the onset of MS.…”
Section: Clinical Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Treatment with OGF or LDN restored serum enkephalin levels to normal and often correlated with reduced clinical behavior and restored sensitivity to pain and heat in mice. The animal work facilitated measurement of serum enkephalins in a longitudinal manner and was able to demonstrate that normal animals inoculated with MOG antigen expressed decreased enkephalins as the disease progressed (47,48). This work is the first to suggest that OGF (chemically termed [Met 5 ]-enkephalin) may be a specific marker for the onset of MS.…”
Section: Clinical Studiesmentioning
confidence: 89%
“…Extension of this work has resulted in studies that have shown that animals with EAE (47,48) or individuals with MS (48) have decreased enkephalin levels. Treatment with OGF or LDN restored serum enkephalin levels to normal and often correlated with reduced clinical behavior and restored sensitivity to pain and heat in mice.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…At a dosage less than 5 mg, LDN acts as a biotherapeutic and modulates the activity of endogenous enkephalins and endorphins [49,50]. In the multiple sclerosis patient population, endogenous [Met 5 ]-enkephalin (i.e., OGF) is reduced when compared to non-multiple sclerosis patients [51]. It is hypothesized that the reduction in serum levels of this inhibitory growth factor are unable to control the increase in T cell proliferation that occurs with immune-related flares.…”
Section: Enkephalins As Therapeutic Treatmentmentioning
confidence: 99%
“…The key component in the mechanistic pathway is the duration of opioid receptor blockade. This work is detailed in animal studies [51][52][53][54][55][56][57]. LDN produces an intermittent blockade of OGFr preventing OGF from binding and thereby increasing cellular replication, similar to what is seen with high doses of Naltrexone (HDN) through a prolonged blockade of OGFr [49].…”
Section: Laboratory Studies On Ldnmentioning
confidence: 99%
See 1 more Smart Citation